1991
DOI: 10.1210/endo-128-4-1792
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Osteoclasts in Osteopetrotic Mice Is Due to a Defect in the Local Microenvironment Provided by Osteoblastic Cells*

Abstract: We have reported that osteoblastic cells are required for differentiation of osteoclast progenitors in splenic tissues into multinucleated osteoclasts. In the present study we examined the pathogenesis of the osteoclast deficiency in osteopetrotic (op/op) mice using a coculture system of spleen cells and osteoblastic cells. When spleen cells obtained from op/op or normal (+/?) littermates of op/+ parent mice were cocultured with osteoblastic cells obtained from calvaria of normal ddy strain mice, numerous tart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 13 publications
4
69
0
Order By: Relevance
“…M-CSF produced by osteoblasts͞stromal cells appears to be essential for the proliferation and differentiation of osteoclast progenitors (27)(28)(29)(30)(31). This is consistent with our observation that M-CSF was indispensable for ODF-mediated OCL formation.…”
Section: Discussionsupporting
confidence: 91%
“…M-CSF produced by osteoblasts͞stromal cells appears to be essential for the proliferation and differentiation of osteoclast progenitors (27)(28)(29)(30)(31). This is consistent with our observation that M-CSF was indispensable for ODF-mediated OCL formation.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of naturally occurring or genetically engineered forms of osteopetrosis indicate that failure of osteoclast formation may result from defects associated with either accessory (osteoblast/stromal) cells or with cells of the osteoclast lineage (Yoshida et al 1990;Soriano et al 1991;Takahashi et al 1991;Wang et al 1992;Grigoriades et al 1994;Tondravi et al 1997). To address this issue we performed in vitro coculture experiments in which the generation of functional osteoclasts from splenic precursors is dependent on supportive stromal cells/osteoblasts.…”
Section: Impaired Development Of Osteoclasts Tracks With This Cell LImentioning
confidence: 99%
“…Two molecules, CSF-1 and MCP-1, are prime candidates for recruiting the osteoclast precursors (mononuclear cells) into the DF. Although it is known that CSF-1 is required for the formation of osteoclasts from monocytes (mononuclear cells) (e.g., see Kodama et al, 1991;Takahashi et al, 1991;Tanaka et al, 1993;Felix et al, 1990b), it also is a chemoattractant for monocytes in vitro (Wang et al, 1988;Bober et al, 1995). Monocyte chemotactic protein-1 (MCP-1) is a well-known chemokine for monocytes (Rollins et al, 1988;Yoshimura et al, 1991) and is found in a variety of cell types, including fibroblasts (Yu and Graves, 1995).…”
Section: (A) Recruitment Of Osteoclast Precursorsmentioning
confidence: 99%
“…The proliferation and differentiation of osteoclast progenitors require CSF-1 (e.g., see Felix et al, 1990b;Kodama et al, 1991;Takahashi et al, 1991;Tanaka et al, 1993). Once the progenitor cells are formed, CSF-1 appears to be indispensable for osteoclast formation (Yasuda et al, 1998a(Yasuda et al, , 1999Jimi et al, 1999).…”
Section: (B) Signaling Pathways In Osteoclastsmentioning
confidence: 99%